2018
DOI: 10.1021/acs.jpcb.7b08563
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Solvation Dominates the Terahertz Fingerprint of Amino Acids in Water

Abstract: Spectroscopy in the terahertz frequency regime is a sensitive tool to probe solvation-induced effects in aqueous solutions. Yet, a systematic understanding of spectral lineshapes as a result of distinct solvation contributions remains terra incognita. We demonstrate that modularization of amino acids in terms of functional groups allows us to compute their distinct contributions to the total terahertz response. Introducing the molecular cross-correlation analysis method provides unique access to these site-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…The THz intensity below 150 cm À1 is predicted to be suppressed for the negative form of the carboxylic acid group compared to the neutral form. 45,47,48 Measurements of glycine confirm this, where it was observed that the negatively charged molecule has a larger intensity than the zwitterionic molecule, 49 and is consistent with results shown in Fig. 2 for PetF.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The THz intensity below 150 cm À1 is predicted to be suppressed for the negative form of the carboxylic acid group compared to the neutral form. 45,47,48 Measurements of glycine confirm this, where it was observed that the negatively charged molecule has a larger intensity than the zwitterionic molecule, 49 and is consistent with results shown in Fig. 2 for PetF.…”
Section: Resultssupporting
confidence: 79%
“…This increased intensity was attributed to cage rattling modes of the solvating water molecules at 65 and 70 cm À1 (1.8 and 2.0 THz). [45][46][47] While the surface of FNR has both positively and negatively charged regions, the positively charged region covers a larger surface area, and the results obtained here show that the contribution of the positively charged groups dominates the THz response. In contrast, PetF has a negatively charged surface, which is mostly comprised of aspartic acid and glutamic acid residues.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we use terahertz (THz) absorption spectroscopy and ab initio molecular dynamics (AIMD) to characterize low-frequency vibrations and structural organization of water in the nanoconfined environment. THz is ideally suited to probe the intermolecular collective dynamics of the water hydrogen bond (HB) network with extremely high sensitivity, as illustrated for different phases of water (33)(34)(35)(36)(37)(38), and for aqueous solutions of salts, osmolytes, alcohols, and amino acids (36,(39)(40)(41)(42). The THz spectra of the water inside the nanocage has been quantitatively reproduced with AIMD, allowing us to confidently characterize the water network in the cage in order to provide a more complete dynamical, structural, and thermodynamic picture.…”
mentioning
confidence: 99%
“…The effective absorption spectrum of solvated glycine in pure water is known to be dominated by the cage librations and rattling modes of the solute within its hydration cage below 100 cm −1 , the glycine‐water hydrogen bond stretching modes at about 200 cm −1 and at the N‐C‐C‐O open/close mode at 315 cm −1 [25, 26] . Upon increasing HCl concentration, we observe an increase in absorption with increasing concentration.…”
Section: Resultsmentioning
confidence: 69%
“…Interestingly, we observe here the same phenomenon: While the N‐C‐C‐O open/close mode is slightly shifted to about 350 and 340 cm −1 , respectively (see Refs. [26] and [31]), we measure for this mode a similar increase in intensity upon protonation, see SI for details.…”
Section: Resultsmentioning
confidence: 99%